2017
DOI: 10.1021/acs.organomet.7b00056
|View full text |Cite
|
Sign up to set email alerts
|

Alane-Centered Ring Expansion of N-Heterocyclic Carbenes

Abstract: The β-diketiminato aluminum dihydrides, [HC­{(Me)­CNAr}2AlH2] [4: Ar = 2,6-di-isopropylphenyl (Dipp), 5: 2,4,6-trimethyl­phenyl (Mes)] react directly with N-aryl-substituted N-heterocyclic carbenes (NHCs) by C–N bond activation to afford aluminum amido-alkyl derivatives of the form [HC­{(Me)­CNAr}2AlCH2(N­(Ar′)­CH)2]. The more sterically congested alane (4), bearing N-Dipp substitution, does not react with either 1,3-bis­(2,6-di-isopropylphenyl)­imidazol-2-ylidene (IPr) or 1,3-bis­(2,4,6-trimethyl­phenyl)­imid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 78 publications
0
32
0
2
Order By: Relevance
“…The NHC−aluminum bond distance of 2.0709(18) Å corresponds to the one observed in ( i Pr 2 Im) ⋅ AlH 3 ( 3 ; 2.0405(17) Å). The Al−C RER‐NHC bond length of 1.999(2) Å and the Al−N RER‐NHC of 1.8514(17) Å do not deviate from the known literature data for Al−C (1.99 Å) and Al−N (1.88 Å) single bonds.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…The NHC−aluminum bond distance of 2.0709(18) Å corresponds to the one observed in ( i Pr 2 Im) ⋅ AlH 3 ( 3 ; 2.0405(17) Å). The Al−C RER‐NHC bond length of 1.999(2) Å and the Al−N RER‐NHC of 1.8514(17) Å do not deviate from the known literature data for Al−C (1.99 Å) and Al−N (1.88 Å) single bonds.…”
Section: Resultsmentioning
confidence: 45%
“…NHC aluminum chemistry has been developed to some extent and it is known that Lewis acid–base adducts of aluminum hydrides are rather unstable. Besides simple decomposition of the compounds to unidentified molecules, NHC to a NHC ( a NHC=abnormal N‐heterocyclic carbene) rearrangement in the coordination sphere of aluminum and ring‐expansion reaction of an NHC in β‐diketiminatoaluminum dihydrides have been observed . However, the utilization of carbenes in aluminum chemistry also facilitates the isolation of interesting substances with new molecular structures, such as (Dipp 2 Im) ⋅ H 2 Al−AlH 2 ⋅ (Dipp 2 Im), obtained by magnesium(I)‐mediated dehydrogenative coupling of (Dipp 2 Im) ⋅ AlH 3 , or a cAAC‐stabilized neutral aluminum radical and the NHC‐stabilized aluminum cation [{(Dipp 2 Im) ⋅ AlH( μ 2 ‐H)} 2 ] 2+ 2[B(C 6 F 5 ) 4 ] − .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Calculations have shown that the five coordinated bis-NHC adducts of group 13 hydrides are higher in energy and less stable than the four coordinated tetrahedral mono NHC adducts and are often intermediates of further reactions. [18] Instead of NHC ring expansion we observe in the case of (NHC) 2 •EH 2 I stabilization by an elimination of the good leaving group iodide to give the four-coordinated tetrahedral aluminium or gallium cation, respectively (see Scheme 4, ii). The strong σ-donating alkyl-substituted NHCs stabilize the cationic electron deficient metal centre in its 8VE count.…”
Section: Resultsmentioning
confidence: 92%
“…Recently we reported the synthesis of a six-coordinated aluminium cation [(iPr 2 Im) 4 •AlH 2 ] + IX as a side product of the reaction of lithium aluminium hydride with an excess of iPr 2 Im (iPr 2 Im = 1,3-diisopropyl-imidazolin-2-ylidene, see Scheme 1, IX). [7] Stephan et al presented [8] Jones and Stasch et al 4, Al1-H2 1.66(4), Al1-I1 2.586 (8); H1-Al1-H2 109.4 (18), H1-Al1-I1 108.7 (12), H2-Al1-I1 106.5 (14), C1-Al1-H1 114.3 (14), C1-Al1-H2 106.5 (14), C1-Al1-I1 105.88(7); 9: C1-Al1 2.039(3), Al1-H1 1.58 (5), Al1-H2 1.60(4), Al1-I1 2.5960 (10); H1-Al1-H2 104(2), H1-Al1-I1 110.5 (17), H2-Al1-I1 111.1 (14), C1-Al1-H1 106.7 (18), C1-Al1-H2 120.2 (14), C1-Al1-I1 103.77(9); 10: Ga-C1 2.036(4), Ga-H1 1.52 (6), Ga-H2 1.44 (7), Ga-I 2.6415 (6). C1-Ga-H1 109(2), C1-Ga-H2 108(2), C1-Ga-I 100.07 (13), H1-Ga-H2 122(3), H1-Ga-I 110(2), H2-Ga-I 105(2).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have very recently reported the first observation of the insertion of an aluminumh ydride at room temperature, [36] which was assisted by the use of aN acNac ligand that servest oi ncreaset he hydridic character in comparison with NHC ligands.…”
Section: Group1mentioning
confidence: 99%